Analysis of battery performance on electric bicycle rear wheel - Muhamad Bakri, Abdul Hamid (2013)
Bicycle basically is a form of simplest transportation method that can be use by us to move from one point to another. In conventional way, the bicycle needs the human who operates it use their own energy to force the bicycle so it can move. So an invention has been created and it was electric bicycle, basically using an electric motor and battery powered to replace the human energy and force. Compare to the normal bicycle, a battery powered electric bicycle delivers the travel distance at lowest possible cost compared to the one who pedals a bicycle and derived muscle energy from food. The main focus for this project is to analyze of battery performance on electric bicycle motor so that that it can achieve all the objective set. The performances of electric bicycles are basis for the data needed from electric motor and the battery. The task included is the fabrication of tire test rig to test the performances of electric motor besides testing the battery. Due to limited sources like the bicycle frame, all the testing is done at the tire test rig for the whole project. The result shows that relationship between voltage and current really significant in the power and speed produce by the electric motor that are really helpful in development of motor controller later. For the future development, there is a hope for fully functioning electric bicycle with a motor controller that have a selective mode for different riding profile.